Copper and Zinc Deficiency in a Patient Receiving Long-Term Parenteral Nutrition During a Shortage of Parenteral Trace Element Products. (November 2015) - Palm, Eric; Dotson, Bryan
Drug shortages in the United States, including parenteral nutrition (PN) components, have been common in recent years and can adversely affect patient care. Here we report a case of copper and zinc deficiency in a patient receiving PN during a shortage of parenteral trace element products. The management of the patient's deficiencies, including the use of an imported parenteral multi–trace element product, is described.